Stability-based assessment of Monteggia-type injuries predicts failure of treatment. Issue 1 (January 2017) - Walton, Roger D.M.; Ormsby, Neal M.; Brookes-Fazakerley, Steven D.; Manohar, Shambavi; Patel, Trupesh; Wright, David M.; Bass, Alf A.; Bruce, Colin E.
Abstract : Paediatric Monteggia-type injuries are complicated by treatment failure and posterior interosseous nerve palsy, without reliable predictive indicators. Outcome is considered to be good, with little patient-reported evidence. We propose novel radiographic parameters. A total of 33 Monteggia-type injuries were analysed. Posterior interosseous nerve palsy was strongly predicted by the Radial Head Displacement Index. The presence of two or more of three novel instability markers was associated strongly with treatment failure. Patient-reported outcome measures were almost uniformly excellent. We advocate the use of a new, inclusive, stability-based classification of Monteggia-type injuries to predict patients who require accurate internal fixation.